Pemanfaatan Herbal untuk Mengurangi Gejala Mual dan Muntah pada Ibu Hamin Trisemster 1 - Fauzia, Lita; Januansyah, Topan (STIKES Yarsi Mataram, 2025)
Emesis gravidarum is a symptom of nausea accompanied by vomiting that occurs early in pregnancy. Emesis gravidarum occurs due to increased levels of the hormones estrogen and progesterone produced by Human Chorionic Gonadotropin (HCG) in the serum from the placenta, in the endocrine system which will stimulate the stomach so that stomach acid increases and causes nausea and vomiting. The frequency of morning sickness is not only in the morning but can be in the afternoon or evening, apart from that it can also occur because of smelling food and air freshener or clothes. Emesis gravidarum is a common complaint that occurs in early pregnancy. The clinical symptom of emesis gravidarum is dizziness, especially in the morning which is usually accompanied by nausea and vomiting. Nausea and vomiting can be treated with herbal plants that are usually recommended by health workers, namely ginger infusion, lime infusion, mint leaf infusion, lemon aromatherapy and turmeric infusion. Objective: The research aims to determine the level. Pregnant women's awareness of the use of herbs and the effectiveness of herbal treatments to reduce nausea and vomiting. Method: The method in this research is quantitative. This research was carried out in West of Penimbung, west Lombok, NTB. This was carried out in May 2024. The sample in this study was all pregnant women who took part in counseling in West Penimbung, , Penimbung Vilage ,West Lombok, NTB, namely 50 pregnant women. The instrument in this study used a questionnaire made on the HVS sheet and in distribute it to pregnant women when the patient is taking anamnesis. The data obtained is analyzed univariately. Results: The results of the study showed that the majority of pregnant women used herbs as an alternative medicine to reduce nausea and vomiting in the 1st trimester, namely 17 patients (34%) using ginger infusion, 13 patients (26%) with lime infusion, 4 patients with mint leaf infusion. (8%), lemon aroma therapy in 4 patients (8%) and turmeric infusion in 2 patients (4%). And the remaining non-herbal therapy in 10 patients (20%). Taking vitamins to relieve nausea and vomiting, consulting a midwife/doctor and for some pregnant women just resting can reduce the nausea and vomiting they experience.